Language-Based Differential Item Functioning in 2021-2022 NECO Chemistry Exams in North Central Nigeria - Ekele, B; Obinne, A D E; Adulojo, M O; Onuh, Omale (Journal of Research in Science and Mathematics Education, 2024)
Purpose: This research examines the presence of Differential Item Functioning (DIF) in the NECO SSCE Chemistry Multiple Choice Test administered in Nigeria's North Central region between 2021 and 2022. DIF refers to differences in test item performance across various student groups. Methodology: Using Classical Test Theory (CTT) and Item Response Theory (IRT) frameworks, the study employed an ex-post-facto design to analyze existing data from 3,012 chemistry students. Statistical methods such as factor analysis, local independence testing, and ability estimation were used for data analysis. Findings: The findings revealed minimal DIF related to language. The study highlights the need to address biases and inequities in test items and provides recommendations for enhancing fairness, validity, and reliability in assessments. Significance: These include revising test items, collaborating with subject experts, offering training on inclusive assessment practices, applying robust sampling techniques, conducting continuous monitoring, and developing targeted interventions to support students affected by DIF.